Deficiência de micronutriente, estado nutricional antropométrico e composição corporal de crianças e adolescentes com doença falciforme em Feira de Santana-BA - Guimarães, Carina Oliveira Silva (2018)
The sickle cell disease (SCD) is a genetic hemoglobinopathy, characterized by the presence of hemoglobin S (HbS) in red blood cells. People with SCD present a high nutritional risk and tend to have vitamin and mineral deficiencies. The objective of this study was to evaluate the deficiencies of vitamin D, A, B12, folic acid, calcium, magnesium and zinc and nutritional status anthropometric and body composition, of people as SCD and correlate them as the genotypes of the disease. A cross-sectional study was carried out with children and adolescents aged 2 to 18 years old, of both sex with SCD, attended at the Reference Unit in our Urban Social Center, Feira de Santana - BA. We excluded from the study individuals using enteral diet via catheter and pregnant women. Sociodemographic, clinical, anthropometric data (weight, height), electrical bioimpedance and serum levels of calcium, magnesium, zinc, vitamin A, 25-hydroxy-vitamin D, folic acid and vitamin B12 were collected. The data were described by their measures of central tendency and dispersion measures. Bivariate analysis was performed between established independent and dependent variables and odds ratio with a respective 95% confidence interval (95% CI) were calculated. Statistical significance was set at p-value ≤ 0.05. The results of this dissertation were presented in the format of two scientific articles. In the first article the micronutrient deficiencies were evaluated, a high prevalence of deficiency of vitamin D and vitamin A was verified, greater of these in individuals with the homozygous form of the SCD (SS). In the second article we evaluated the anthropometric nutritional status and body composition, we observed a prevalence of thinness, higher than that observed in the general population, and overweight on the rise, and children and adolescents with homozygous genotype (SS) presented a Z-score of BMI/I significantly lower than the heterozygotes (SC/SF). The findings of the study reveal that children and adolescents with SCD are susceptible to nutritional risk (micronutrient deficiency and weight / height deficit) and overweight. The importance of the monitoring of these parameters in this population is emphasized, with the intention of minimizing the diseases and providing a better quality of life.